Applications of Sensor Networks - Hof, Hans-Joachim (Algorithms for Sensor and Ad Hoc Networks, 2007)
Networks of small sensor nodes, so-called sensor networks, allow to monitor and analyze complex phenomena over a large region and for a long period of time. Recent advances in sensor network research allow for small and cheap sensor nodes which can obtain a lot of data about physical values, e.g. temperature, humidity, lightning condition, pressure, noise level, carbon dioxide level, oxygen level, soil makeup, soil moisture, magnetic field, current characteristics of objects such as speed, direction, and size, the presence or absence of certain kinds of objects, and all kinds of values about machinery, e.g. mechanical stress level or movement. This huge choice of options allow to use sensor network applications in a number of scenarios, e.g. habitat and environment monitoring, health care, military surveillance, industrial machinery surveillance, home automation, als well as smart and interactive places. The application of a sensor network usually determines the design of the sensor nodes and the design of the network itself. No general architecture for sensor networks exists at the moment. This chapter gives an overview of existing sensor network applications, shows some currently available sensor network hardware platforms and gives an outlook on upcoming applications for sensor networks.